Clinical Care for Opioid-using Pregnant and Postpartum Women: The Role of Obstetric Providers. Issue 2 (June 2015) - Jones, H.E.; Deppen, K.; Hudak, M.L.; Leffert, L.; McClelland, C.; Sahin, L.; Starer, J.; Terplan, M.; Thorp, J.M.; Walsh, J.; Creanga, A.A.
Abstract : ( Am J Obstet Gynecol . 2014;210(4):302–10)